(untitled) - Garrett, Reginald H. (Belmont, CA, 2005)
In Biochemistry, the questions often are more exhilarating than the answers. This Updated Third Edition continues the unique conceptual and organizing framework, "Essential Questions." Guiding students through the density of the material by the use of section head questions, supporting concept statements, and summaries, this focused approach is supported by unparalleled text/media integration through BiochemistryNow, providing students with a seamless learning system. Beautifully and consistently illustrated, this text gives science majors the most current presentation of biochemistry available. Written by a chemist and a biologist, the book presents biochemistry from balanced perspectives. This Updated Edition includes "Emerging Insights into Biochemistry" at the end of each chapter, which present students with the latest advances in biochemical research. The Updated Edition also is enhanced by the power of the online assessment-centered learning tool, BiochemistryNow. This powerful online learning companion helps students gauge their unique study needs and provides them with a Personalized Learning plan that enhances their problem-solving skills and conceptual understanding.
Keywords: Biochemistry